2012
DOI: 10.1002/ijc.27383
|View full text |Cite
|
Sign up to set email alerts
|

Body mass index change in adulthood and lung and upper aerodigestive tract cancers

Abstract: Body-mass-index (BMI) has been inversely associated with lung and upper aerodigestive tract (UADT) cancers. However, only a few studies have assessed BMI change in adulthood in relation to cancer. To understand the relationship between BMI change and these cancers in both men and women, we analyzed data from a population-based case-control study conducted in Los Angeles County. Adulthood BMI change was measured as the proportional change in BMI between age 21 and one year prior to interview or diagnosis. Five … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 43 publications
3
11
0
Order By: Relevance
“…Similar results have been reported in a population-based case–control study [31]. BMI gain of more than 25% was associated with a lower risk for lung cancer (OR 0.53, 95% CI 0.33-0.84) and UADT cancers (OR 0.44, 95% CI 0.27-0.71), especially in cigarette smokers and alcohol drinkers [31]. In our study, we have found that every 1-kg/m 2 increment in BMI was inversely associated with risk for synchronous esophageal neoplasia (OR 0.87, 95% CI 0.76-0.99) in H&N cancer patients (Table  2).…”
Section: Discussionsupporting
confidence: 91%
“…Similar results have been reported in a population-based case–control study [31]. BMI gain of more than 25% was associated with a lower risk for lung cancer (OR 0.53, 95% CI 0.33-0.84) and UADT cancers (OR 0.44, 95% CI 0.27-0.71), especially in cigarette smokers and alcohol drinkers [31]. In our study, we have found that every 1-kg/m 2 increment in BMI was inversely associated with risk for synchronous esophageal neoplasia (OR 0.87, 95% CI 0.76-0.99) in H&N cancer patients (Table  2).…”
Section: Discussionsupporting
confidence: 91%
“…Regarding the demographic risk factors, we found that ABCs were strong determinants that led to a lower BMI, indicating poor nutritional status. This finding of the inverse association with UADT cancer risk was keeping with previous reports …”
Section: Discussionsupporting
confidence: 93%
“…This finding of the inverse association with UADT cancer risk was keeping with previous reports. 38,39…”
Section: Main Findings Of Our Studymentioning
confidence: 99%
“…[5][6][7]9,35,36 A decrease in BMI since age 20 has also been associated with an elevated risk for lung cancer mortality among current smokers in one study. 37 Similar to ours, these studies had information on weight at two points in time: at study enrollment and during early adulthood.…”
Section: Epidemiologymentioning
confidence: 96%